Towards a multi-physics modelling framework for thrombolysis under the influence of blood flow - Xu,XY; Piebalgs,A (Journal of the Royal Society Interface, 2015)
Thrombolytic therapy is an effective means of treating thromboembolic diseases but can also give rise to life-threatening side-effects. The infusion of a high drug concentration can provoke internal bleeding while an insufficient dose can lead to artery reocclusion. It is hoped that mathematical modelling of the process of clot lysis can lead to a better understanding and improvement of thrombolytic therapy. To this end, a multi-physics continuum model has been developed to simulate the dissolution of clot over time upon the addition of tissue plasminogen activator (tPA). The transport of tPA and other lytic proteins is modelled by a set of reaction-diffusion-convection equations, while blood flow is described by volume-averaged continuity and momentum equations. The clot is modelled as a fibrous porous medium with its properties being determined as a function of the fibrin fibre radius and voidage of the clot. A unique feature of the model is that it is capable of simulating the entire lytic process from the initial phase of lysis of an occlusive thrombus (diffusion-limited transport), the process of recanalization, to post-canalization thrombolysis under the influence of convective blood flow. The model has been used to examine the dissolution of a fully occluding clot in a simplified artery at different pressure drops. Our predicted lytic front velocities during the initial stage of lysis agree well with experimental and computational results reported by others. Following canalisation, clot lysis patterns are strongly influenced by local flow patterns which are symmetric at low pressure drops, but asymmetric at higher pressure drops which give rise to larger recirculation regions and extended areas of intense drug accumulation.